Political-Economy of Social Entrepreneurship in Indonesia: A Polanyian Approach - Tadzkia Nurshafira; Rizky Alif Alvian (Jurnal Ilmu Sosial dan Ilmu Politik, 2018)
This paper attempts to develop a critical analysis on the concept of social entrepreneurship (SE) in Indonesia in comparison to that in the Global North. Departing from Karl Polanyi’s theorization of market society, this paper asserts that the concept of SE embodies a ‘double movement’. It embodies a tension between the ‘dis-embedding movement’ (attempts to organize society according to market rationality) and the ‘re-embedding movement’ (attempts to ensure that the market works to serve society’s interests), that is, between a formal and a substantive approach to the economy. The rise of SE, therefore, is always situated within a particular politico-economic context. Using Indonesia’s experience as a case study, this paper argues that the emergence of SE is strongly influenced by Widodo’s economic nationalism ideology. In this regard, SE is largely a part of Widodo’s strategy for bolstering economic growth, particularly by stimulating the rise of local entrepreneurs. Within such a framework, the nature of SE as a tool for addressing social problems is insufficiently recognized. SE in Indonesia therefore embodies tensions between the dis-embedding and re-embedding movements. The dis-embedding movement, however, prevails in Indonesia.